186 OPTIMAL MANAGEMENT OF COVID-19 IN NURSING HOME PATIENTS: A QUALITY IMPROVEMENT PROJECT IN AN IRISH UNIVERSITY HOSPITAL EMERGENCY DEPARTMENT. (18th November 2021) - Foley, J; Menzies, D; Boyle, N; McNamara, R
Abstract: Background: The Sars-CoV-2 global pandemic placed an unprecedented demand on acute health services and led to significant morbidity and mortality in older populations. Nearly half of attendances to this ED are over the age of 65 years and there are over 80 nursing homes in the catchment area. A pilot study in January 2021 showed that nursing home attendances increased significantly during the third wave of COVID-19 with many of these attendances potentially avoidable and suitable for optimised care in the nursing home. The primary objective of this quality improvement project was to enhance the older person's care and experience when presenting to ED or being reviewed in the community with symptoms and signs of COVID-19. Secondary aims were reduced nursing home attendances to ED and subsequent admissions from these attendances. Methods: A guideline was constructed based on the RCEM standard for Quality Care for Older People and using the HSE guidelines for managing COVID-19 in nursing home patients. The guideline was introduced to staff and implemented in ED and via the EDITH service. Results: Two PDSA cycles were undertaken post guideline implementation. There were substantial improvements in the frequency of discussion and documentation of advanced directives with increased numbers of patients being discharged directly back to the nursing home or treated in the nursing home using the guideline. There was a decrease in the number of nursing home attendances throughout the project. Conclusion: This successful QIP shows the importance of manging older patients appropriately, while considering their wishes. Post-COVID work should centre on managing all older patients with optimised treatment and considering how they will benefit most from their attendance to ED.